Basic environmental assessment of the construction area - A. L. Bolsherotov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of this work is to develop a methodology for an objective assessment of the environmental safety of construction sites and development areas.Method. The study is based on a conceptual approach to assessing the environmental safety of construction sites and territories.Result. A methodology for assessing the environmental safety of construction objects is proposed; the criteria for assessing the development area are determined; methods for solving the problems of development of territories and their environmental safety are proposed. As a method of assessment, the coefficient "degree of real estate concentration" was developed and adopted. The concepts of "environmental reserve", "threshold of environmental safety", "sustainable state range" are introduced, which makes it possible to reliably assess the possibilities of territories for the placement of construction objects with different technogenic potential.Conclusion. It is necessary to legislate, as a mandatory procedure, the procedure for assessing the “degree of concentration of real estate” in administrative territories, especially when planning the construction of a housing stock under the renovation program, when allocating land for new construction, when assessing the environmental impact in the design and examination of construction projects.